Biodiesel from rapeseed oil (Brassica napus) by supported Li2O and MgO - Solis, Jerry L.; Berkemar, Albin L.; Alejo, Lucio; Kiros, Yohannes (International Journal of Energy and Environmental Engineering, 2016)
Abstract Vegetable oils are a vast triglyceride source for biodiesel production; i.e. fatty acid methyl esters (FAME), with methanol and a catalyst via transesterification reaction. The aim of this work was to study heterogeneously catalysed biodiesel production with solid oxides such as mayenite (Ca 12 Al 14 O 33 ) and alumina (Al 2 O 3 ) as catalyst carriers using edible rapeseed oil as feedstock. These oxides were impregnated to have Li 2 O and MgO concentrations of 5–10 and 5–30 wt% on each carrier, respectively. The catalysts were characterized using N 2 -physisorption (BET/BJH), scanning electron microscopy (SEM), and X-ray diffraction (XRD) analyses. The synthesized catalysts were mesoporous ranging from 119 to 401 Å and their chemical phase composition was confirmed by the XRD. The catalyst coating (MgO/Li 2 O) was studied, along with the catalyst amount in the reactor and the assessment of the transesterification reaction kinetics. The reaction was studied at 60 °C, atmospheric pressure, agitation rate of 180 rpm, and a reaction time of 2 h in a 6:1 molar ratio of methanol to oil. For each catalyst, loadings of 2.5, 5, and 10 wt% relative to the oil weight were evaluated. The highest biodiesel yield was obtained by 5 wt% (relative to oil weight) impregnated mayenite catalyst coated with 10 wt% of Li 2 O. The kinetic data fits to a pseudo-first-order model having a reaction rate constant equal to 0.045 min −1 under these mild reaction conditions.